2021
DOI: 10.12944/crnfsj.9.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Nutritional Status and Habits of Students Studying in Private and Government Schools in a Semi-Urban Town in India –Kumbakonam Urban Rural Epidemiological Study - KURES -1

Abstract: Malnutrition is a universal and an ever-rising problem due to changes in the lifestyle and eating habits among the children. The malnourished children are prone to illness. Hence, we planned to conduct a study in school children, both in Government set up and a private set up, to review their nutritional status and the influencing factors. Two thousand students in the age group of 8-17 years were interviewed for their food habits, asking them to fill up a proforma along with anthropometric measurements. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Even though children in private schools are better fed, the underweight rate remains at 58.6%. They are comparable to children from government schools regarding playing times, dietary habits, and sleeping patterns 8 . It is critical to promote sports among children of all socioeconomic backgrounds.…”
Section: Discussionmentioning
confidence: 78%
“…Even though children in private schools are better fed, the underweight rate remains at 58.6%. They are comparable to children from government schools regarding playing times, dietary habits, and sleeping patterns 8 . It is critical to promote sports among children of all socioeconomic backgrounds.…”
Section: Discussionmentioning
confidence: 78%
“…Nutrition education on junk foods, their health hazards, and promoting healthy behavior successfully improved school children's knowledge. 1 Suchitra et al 19 found that two thousand students between the ages of 8 and 17 were interviewed about their eating habits and asked to complete proforma and anthropometric measurements. Seventy-two percent of the children questioned were malnourished, but only 0.06% were obese.…”
Section: Nutrition Education and Knowledgementioning
confidence: 99%